Prognostic role of different PD-L1 expression patterns and tumor-infiltrating lymphocytes in high-grade serous ovarian cancer: a systematic review and meta-analysis - Wang, Ye-Min; Cai, Wei; Xue, Qing-Ming; Zhang, Jin-Yao; Zhou, Lv; Xiong, Su-Yi; Deng, Huan (Frontiers in Immunology, 2023)
Background: The prognostic value of programmed cell death ligand 1 (PD-L1) expression and tumor-infiltrating lymphocytes (TILs) in high-grade serous ovarian cancer (HGSOC) remains a controversial topic in the research field. To comprehensively assess the importance of PD-L1 and TILs in this particular subtype of ovarian cancer, we performed a meta-analysis. Methods: We conducted a comprehensive search of PubMed, Embase, Scopus, Web of Science, and Cochrane Library databases up to December 25, 2022. The association between PD-L1, TILs, and survival outcomes was evaluated using the combined hazard ratios (HRs) and their corresponding 95% confidence intervals (CIs). Results: This meta-analysis comprised 11 trials involving a total of 1746 cases. The results revealed no significant association between PD-L1 expression in tumor cells (TCs) and overall survival (OS, HR = 0.76, 95% CI: 0.52-1.09, p = 0.136) or progression-free survival (PFS, HR = 0.71, 95% CI: 0.4 -1.24, p = 0.230). Nevertheless, a correlation was observed between PD-L1 expression in immune cells (ICs) and OS (HR = 0.73，95% CI：0.55-0.97，p = 0.031). Furthermore, the presence of CD8+ and PD-1+ TIL was found to significantly enhance OS (HR = 0.70，95% CI = 0.55-0.87，p = 0.002；HR = 0.57，95% CI = 0.40-0.80，p = 0.001, respectively) and PFS (HR = 0.62, 95% CI = 0.41-0.92, p = 0.019; HR = 0.52, 95% CI = 0.35-0.78, p = 0.002, respectively), whereas the presence of CD3+ and CD4+ TIL was positively associated with OS (HR = 0.50, 95% CI = 0.29-0.87, p = 0.014; HR = 0.55, 95% CI = 0.34-0.91, p = 0.020, respectively). Conclusions: This study indicates a positive correlation between ICs-derived PD-L1 and survival, while no significant correlation was observed between TCs-derived PD-L1 and prognosis. These results highlight the importance of studying PD-L1 expression in ICs as a prognostic predictor. In addition, the presence of TILs was found to significantly improve patient survival, suggesting that TILs may be a valuable prognostic biomarker.